Respuesta :
Step-by-step explanation:
sin(theta)÷costheta+sintheta/sintheta÷COStheta- sintheta
sintheta+sintheta×costheta/sintheta-sintheta-costheta
sintheta(1+Costheta)/sintheta(1-costheta)
1+1÷Sectheta/1-1÷Sectheta
sectheta+1÷sectheta/sectheta-1÷sectheta
sectheta+1/sectheta-1
Answer:
TO PROVE :-
- [tex]\frac{\tan \theta + \sin \theta}{\tan \theta - \sin \theta} = \frac{\sec \theta + 1}{\sec \theta - 1}[/tex]
SOLUTION :-
First of all , simplify L.H.S.
[tex]\frac{\tan \theta + \sin \theta}{\tan \theta - \sin \theta}[/tex]
- Use [tex]\tan \theta = \frac{\sin \theta}{\cos \theta}[/tex] in place of tanθ.
[tex]=> \frac{\frac{\sin \theta}{\cos \theta} + \sin \theta }{\frac{\sin \theta}{\cos \theta} - \sin \theta}[/tex]
- Take sinθ common from both numerator & denominator.
[tex]=> \frac{\sin \theta (\frac{1}{\cos \theta} + 1) }{\sin \theta (\frac{1}{\cos \theta}- 1) }[/tex]
- Cancel the sinθ from both numerator & denominator.
[tex]=> \frac{\frac{1}{\cos \theta} +1}{\frac{1}{\cos \theta} -1}[/tex]
- Use [tex]\sec \theta = \frac{1}{\cos \theta}[/tex]
[tex]=> \frac{\sec \theta + 1}{\sec \theta - 1}[/tex]
∴ L.H.S. = R.H.S